A Review on Household Water End-Use Consumption to Mitigate the Urban Water Crisis: Insight from Various Cities in Indonesia. Issue 1 (1st October 2022) - Azizah, R N; Sinaga, L F; Awfa, D; Imami, A D; Yanda, R; Saraswati, Z F; Putri, Y; Setiawati, E
Abstract: The present paper reviews the recent perspectives of end-use studies as a part of urban water crisis mitigation within the past decade in various regions in Indonesia. The paper integrates a critical review of water-end use consumption from five major islands in Indonesia. Comparative methods were used to determine the domestic water consumption behaviour from the collected data from 2013 to 2020. Furthermore, the collected data were classified into two major groups (i.e., regions on Java Island and regions on non-Java Island). At the end, this review reflected a different pattern between domestic water consumption in various socio-economic regions in Indonesia and expected to provide strategies that could be used to mitigate the urban water crisis in the future.